1994
DOI: 10.1111/j.1600-0714.1994.tb01100.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exposure to chlorhexidine gluconate in vitro and in vivo on in vitro adhesion of Candida albicans to buccal epithelial cells from diabetic and non‐diabetic subjects

Abstract: The effect of 0.2% chlorhexidine gluconate on in vitro adhesion of Candida albicans to buccal epithelial cells (BEC) was studied in 12 healthy subjects and 12 patients with diabetes mellitus. Exposure of BEC for one minute with 0.2% chlorhexidine gluconate in vitro, or by rinsing the mouth in vivo, resulted in a significant reduction in candidal adhesion to BEC in both diabetic and non-diabetic subjects and between both groups. In addition to the known fungicidal effect of chlorhexidine, it also reduces Candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
1
25
0
2
Order By: Relevance
“…The CHX mouthwash has the highest efficiency to reduce germ tube of C. albicans. Similar results were reported by others and showed that CHX mouthwashes reduced C. albicans adhesion to BEC and germ tube formation significantly (Darwazeh et al, 1994;Ellepola and Samaranayake, 2000;Pizzo et al, 2001). CHX decreased epithelial-cell membrane-lipid packing order, particularly in superficial regions, similar to antifungal drug used for detachment of adherent yeasts (Audus et al, 1992).…”
Section: Resultssupporting
confidence: 78%
“…The CHX mouthwash has the highest efficiency to reduce germ tube of C. albicans. Similar results were reported by others and showed that CHX mouthwashes reduced C. albicans adhesion to BEC and germ tube formation significantly (Darwazeh et al, 1994;Ellepola and Samaranayake, 2000;Pizzo et al, 2001). CHX decreased epithelial-cell membrane-lipid packing order, particularly in superficial regions, similar to antifungal drug used for detachment of adherent yeasts (Audus et al, 1992).…”
Section: Resultssupporting
confidence: 78%
“…other than C. albicans, such as C. glabrata, Candida tropicalis and C. krusei [13,17]. It has also been shown to have superior efficacy against Candida biofilms compared with FLZ in vitro and in vivo [13,[18][19][20][21]. Furthermore, it can be used to impregnate denture liners to act as a long-term self-release drug carrier [22].…”
Section: Introductionmentioning
confidence: 97%
“…The antifungal effect of chlorhexidine gluconate has been demonstrated in several in vivo and in vitro trials, including some related to Candida infection [9]. Further, it has been demonstrated that exposure of either Candida isolates or buccal epithelial cells to 0.2% chlorhexidine gluconate profoundly suppressed their ability to adhere to buccal epithelial cells in healthy individuals [10] as well as in diabetics [11]. Moreover, pretreatment of acrylic dentures with 2% chlorhexidine gluconate has also been shown to suppress the adhesion of Candida to the denture's acrylic surfaces [12].…”
Section: Introductionmentioning
confidence: 99%